2001
DOI: 10.1046/j.1365-2133.2001.04225.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet AI exposure of human skin results in Langerhans cell depletion and reduction of epidermal antigen-presenting cell function: partial protection by a broad-spectrum sunscreen

Abstract: In vivo UVAI exposure of human skin results in a decreased number of ELC and in a downregulation of epidermal APC activity. This last effect is partially prevented by prior application of a sunscreen with a low UVAI-PF value. These results indicate that increasing the absorption of UV filters for long UVA wavelengths may lead to an improved immune protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 38 publications
4
66
1
1
Order By: Relevance
“…SC, since it is the outer part of the epidermis [17][18][19], is identified as the main target of oxidative damage [20]. SC ·-tocopherol is decreased by UV exposure [9,14,21] and it is found to be effective against UV-induced immunosuppression [22], tumorigenesis [22], lipid peroxidation [23][24][25], chronic skin damage and tumors, erythema, 'sunburn cell' formation [26], epidermal Langerhans cell depletion [27,28], oxidative DNA damage, genotoxicity and reactive intermediates [29,30]. Vitamin E is probably the most widely investigated photoprotective substance besides sunscreens both of which are almost always present in skin care products.…”
Section: Environmental Stressors and Antioxidant Skin Networkmentioning
confidence: 99%
“…SC, since it is the outer part of the epidermis [17][18][19], is identified as the main target of oxidative damage [20]. SC ·-tocopherol is decreased by UV exposure [9,14,21] and it is found to be effective against UV-induced immunosuppression [22], tumorigenesis [22], lipid peroxidation [23][24][25], chronic skin damage and tumors, erythema, 'sunburn cell' formation [26], epidermal Langerhans cell depletion [27,28], oxidative DNA damage, genotoxicity and reactive intermediates [29,30]. Vitamin E is probably the most widely investigated photoprotective substance besides sunscreens both of which are almost always present in skin care products.…”
Section: Environmental Stressors and Antioxidant Skin Networkmentioning
confidence: 99%
“…It was proved by Dumay et al that UVA1 (340-400 nm) with a dose of 60 J/cm 2 resulted in a lower HLA-DR expression [8]. After exposure of LCs in mice to UVB with a dose 200 J/m 2 , Denfeld et al observed an altered expression of costimulatory molecules CD80 (B7.1) and CD86 (B7.2) (ligands for CD28 in the interaction between LCs and T cells) [24].…”
Section: Effects Of Uv On Morphology and Phenotype Of Lcsmentioning
confidence: 99%
“…Similarly, single doses of UVA1 caused also a decrease in the number of LCs in human epidermis [7,8].…”
Section: Effects Of Uv Radiation On the Number Of Lcs In The Epidermismentioning
confidence: 99%
See 2 more Smart Citations